Talent identification and development in dance: a review of the literature - Walker, I. J.; Nordin-Bates, S. M.; Redding, E. (Research in Dance Education, 2010)
Talent identification and development processes are important components of many dance programmes, yet talent is notoriously difficult to define and its identification may rely on intuitive judgements. Taking a systematic approach to the study of dance talent could enable researchers and educators to better determine what talent actually is, the multi-faceted components that exist within talent and subsequently how best it can be optimised. The aim of this paper is to review existing literature relating to aspects of dance talent. While not attempting to define talent nor provide a guide for identification, the review reports on existing relevant literature that describes the characteristics associated with talent in the hope that it will be valuable to educators and researchers. Further research into the characteristics of talented dancers may enable teachers to prepare their students optimally for the exciting opportunities that dance can offer.